Development Of Infographic Media Based On Qr Code Situs Duplang In History Learning With ASSURE Model - Ar, Hofi Hannan; Soepeno, Bambang; Na'im, Mohammad; Puji, Rully Putri Nirmala; Triyanto, Jefri Rieski; Prasetyo, Guruh (History Education, University of Jember, 2022)
Learning media that serves as a communication tool used in learning, but learning media ccan be beneficial as a means in education which helps the teaching process so that learning does not seem static, so learning can be effective. 05 Jember, SMAN 02 Tanggul and SMAN Arjasa. (1) 66% of educators have difficulties in teaching history in the application of media learning, 33% in teaching methods; (2) The learning method used by educators has used the 100% Lecture method, 66% Problem Solving, 66% Discussion; (3) 66% educators add teaching media in the form of visual Power Point and 66% Video; (4) Educators have obstacles in the application of media in 66% Difficulty in designing learning media, 33% Difficulty in developing learning media. The facilities and infrastructure in the three schools are adequate, from Wi-Fi to projectors, but they are still lacking in utilization in the learning process Based on the questionnaire analytical of learning styles, it must be said that visual teaching styles are 48.3%, audio learning styles are 20.9% and kinesthetic learning styles are 40.7%. improvement of student teaching outcomes after use Infographics teaching media based on Qr Code. The increase in learning outcomes that increased significantly between the pre-test and post-test scores increased the average learning outcomes of students by 87.47%. This Qr Code-based Infographic Media Duplang Site has been developed by adding ideas and concepts to the media. Keywords: Infografis, Qr Code, Situs Duplang